Impact of FDI and FII on the Indian Stock Market during Recent Recession Period: An Empirical Study - Banerjee, Arindam (Journal of Management and Science, 2013)
The era 90‘s saw very significant policy changes introduced in the sphere of financial sector, foreign trade, public sector and social sector. The year 1991 witnessed the process of liberalization and globalization that hit the Indian economy and pushed our country to break open the ―Inward Looking‖ policy when the emphasis was accorded to protectionism and import substitution. Since 1991, India has proved to be a key player in the world. Ours country interaction has increased with many economies ties, political harmony, tourism trade and services more significantly in the area of investment. The present study was conducted by me with the aim to understand the impact of FDI and FII on Indian Stock Market (BSE and Nifty) during the recession period. It was found from the study that FDI had a significant influence on the Indian Stock market during recession while FII negatively influenced the Indian Stock Market.